2016
DOI: 10.1093/cvr/cvw004
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine-1-phosphate reduces ischaemia–reperfusion injury by phosphorylating the gap junction protein Connexin43

Abstract: Our study reveals an important molecular pathway by which modulating the apoM/S1P axis has a therapeutic potential in the fight against I/R injury in the heart.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 44 publications
3
45
0
1
Order By: Relevance
“…Another study also demonstrated that S1P 2 and S1P 3 antagonists block S1P mediated cardioprotection [65]. The studies reported here show that signaling via the S1P 3 receptor to RhoA in cardiomyocytes of the isolated, perfused heart is both sufficient and required for cardioprotection in ex vivo I/R.…”
Section: Discussionsupporting
confidence: 66%
“…Another study also demonstrated that S1P 2 and S1P 3 antagonists block S1P mediated cardioprotection [65]. The studies reported here show that signaling via the S1P 3 receptor to RhoA in cardiomyocytes of the isolated, perfused heart is both sufficient and required for cardioprotection in ex vivo I/R.…”
Section: Discussionsupporting
confidence: 66%
“…HDL infusion or S1P 1 agonists have been previously shown to protect the myocardium from MI/R injury (3841). The effect of ApoM-Fc–S1P was associated with reduced infiltration of neutrophils into the myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, HDL from apoM-TG mice stimulates S1P–dependent signaling mechanisms in endothelial cells while HDL from apoM null mice does not (87). The relationship between apoM expression and S1P-mediated cardioprotection has been recently evaluated in wildtype and transgenic mice undergoing coronary artery ligation and reperfusion (88,89). Plasma S1P levels were increased in apoM-TG mice by approximately 250% compared to wildtype mice.…”
Section: Sphingosine 1-phosphate and Cardioprotectionmentioning
confidence: 99%
“…In vitro analyses of neonatal rat ventricular cardiomyocytes showed that S1P induced phosphorylation of Connexin43 (Cx43) and reduced gap junctional communication between cardiomyocytes (88). It was proposed that S1P protects the heart against I/R injury by inhibiting cell-cell coupling (88,89). In this manner, the passage of death signals through gap junctions is reduced, resulting in attenuation of I/R-induced cardiomyocyte injury (89).…”
Section: Sphingosine 1-phosphate and Cardioprotectionmentioning
confidence: 99%
See 1 more Smart Citation